The ants (Hymenoptera:formicidae) of Rawdhat Khorim Nature Preserve, Saudi Arabia, with description of a new species of the genus Tetramorium Mayr - Sharaf, Mostafa R.; Abdel-Dayem, Mahmoud S.; Dhafer, Hathal M. Al; Aldawood, Abdulrahman S. (Zootaxa, 2013)
Rawdhat Khorim, a densely vegetated alluvial basin supporting a distinctive floral community in the hyper-arid desert of central Saudi Arabia, is one of the most important protected nature sanctuaries of the country. The ant fauna (Formicidae) of Rawdhat Khorim was sampled and 14 species, including one new species were collected using a variety of sampling methods. The new species, Tetramorium saudicum sp. n., a member of the T. caespitum-group, is described based on the worker caste. Cataglyphis viaticoides (André) is recorded for the first time from Saudi Arabia. The information in this paper will allow natural resource managers to establish long-term ecological studies, using sentinel taxa such as ants to evaluate present and future impacts on Rawdhats.